2019
DOI: 10.1002/eat.23029
|View full text |Cite
|
Sign up to set email alerts
|

Why is premorbid BMI consistently elevated in clinical samples, but not in risk factor samples, of individuals with eating disorders?

Abstract: Body image disturbance is widely viewed as contributing to the development and maintenance of disordered eating. Yet this perspective is not inconsistent with the possibility that elevated premorbid BMIs also increase the risk of developing eating disorders. Research examining whether actual body size may play a role in eating disorder development reveals a curious pattern of findings. Few prospective risk factor studies conducted with community-based samples found a relationship between premorbid BMI and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…These findings question the biological validity of TWS but support the biological validity of DWS. Because DWS represents weight lost from highest past premorbid z‐ BMI, this reinforces our previous conclusion (Muratore & Lowe, 2019) that elevated z‐BMIs during development represent a risk factor for the later development of BN.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings question the biological validity of TWS but support the biological validity of DWS. Because DWS represents weight lost from highest past premorbid z‐ BMI, this reinforces our previous conclusion (Muratore & Lowe, 2019) that elevated z‐BMIs during development represent a risk factor for the later development of BN.…”
Section: Discussionsupporting
confidence: 88%
“…The current study differs from the previous one in that it only examines physiological and body composition outcomes. Participants needed to be seeking or in treatment, because prior evidence suggests that WS is more pertinent to clinical than non‐clinical samples with BN (Muratore & Lowe, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism by which this differential effect operates remains unknown, but it is well known that obesity and disordered eating are closely related traits [47]. Overweight individuals are more likely to be involved in binge eating episodes, because of more intense body dissatisfaction and weight suppression [48], which may favor a more pronounced response to job strain and work-family conflict among them. Furthermore, evidence indicates that BMI-related genes are also related to binge eating susceptibility [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…While AN is characterized by significantly low body weight and intense fear of gaining weight, BN is characterized by episodes of bingeing on food followed by compensatory behaviors (Black & Grant, 2014; Mitchell & Peterson, 2020). Despite several studies investigating the relationship between birthweight and childhood body mass index (BMI), and later risk of eating disorders, the evidence remains conflicting (Marzola et al, 2021; Muratore & Lowe, 2019; Stice, 2016). It has been highlighted that higher BMI is related to lower risk of eating disorders primarily in studies based on the general population, whereas the opposite is found in retrospective studies based on clinical samples (Muratore & Lowe, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite several studies investigating the relationship between birthweight and childhood body mass index (BMI), and later risk of eating disorders, the evidence remains conflicting (Marzola et al, 2021; Muratore & Lowe, 2019; Stice, 2016). It has been highlighted that higher BMI is related to lower risk of eating disorders primarily in studies based on the general population, whereas the opposite is found in retrospective studies based on clinical samples (Muratore & Lowe, 2019). Further, the authors emphasized that AN and BN should be studied separately since some studies have indicated that premorbid BMI differs between different eating disorders (Stice, 2016; Stice et al, 2022; Yilmaz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%